Os agentes do Instituto de Pesquisas e Estudos Sociais (IPÊS) e suas carreiras públicas federais : entre a continuidade burocrática e a colonização do Estado pós-1964 - Moraes, Thiago Aguiar de (2016)
This thesis aims to examine the matter of the alleged colonization of the State after 1964 by agents of the Instituto de Pesquisa e Estudos Sociais (IPÊS). In order to do so, the thesis analyzes the time of service and the which federal public offices were held before and after the Coup of 1964 by persons that worked for the IPÊS, as well as their technical background and role inside the institution. The IPÊS was founded by military and civilllians to defend “democracy” from “communism” and influence public policies shortly after Jânio Quadros' stepped down and João Goulart ascended to the presidency. Historiography regarding the period assumes there was a colonization of the State by the ipesianos after 64, as they assumed key positions of power. In order to examine the matter, a prosopographical study of 118 ipesianos was made.